Effect of Processing Conditions on Nitrogen Loss of Sewage Sludge Composting. Issue 3 (1st October 2020) - Ma, Te
Abstract: As a by-product of municipal sewage treatment, sewage sludge must be properly treated to avoid secondary pollution to the environment. Aerobic composting is one of the mainstream technologies in sludge treatment, but nitrogen loss in composting process usually reaches more than 40%, which seriously reduces the fertilizer efficiency of composting products, and at the same time, a large amount of odor will cause harm to the environment. In this article, the nitrogen emission and nitrogen loss were reduced by adding sawdust of different proportions in the sludge composting process, and the nitrogen emission and nitrogen loss were reduced by up to 70% and 30% respectively. The addition of sawdust can significantly increase the sludge composting temperature and duration of high temperature period, reduce the sludge pH and water content, increase the mineralization rate of organic matter, thereby inhibiting the nitrogen loss. The results showed that nitrogen loss decreased with the increase of sawdust ratio, and A30 was the best ratio. The process has the advantages of simple operation, low cost and good nitrogen holding effect.